Rubus prissanicus (Rosaceae), a new bramble species from North West Poland - Kosiński, Piotr; Maliński, Tomasz; Sliwinska, Elwira; Zieliński, Jerzy (Phytotaxa, 2018)
Rubus prissanicus, a new regional apomictic species, is described from north-western Poland. It is similar to R. lindleianus and R. langei, however it differs from the former species by broader leaflets and less numerous prickles on the inflorescence axis, and from the latter by unequally serrate leaflet margin, and from both these species by different types of trichomes on abaxial leaflet surface. Unlike other Polish species of R. ser. Rhamnifolii, in which the indumentum of abaxial leaf surface consists mainly of branched hairs, simple trichomes are the main component of indumentum of R. prissanicus leaves. The new species has been observed mainly on fertile soils, in broadleaf forest habitats, usually in fairly sunny places, along forest margins, by forest roads, in clearings, and in wayside thickets.